Essential Oil Composition from the Aerial Parts of Ajuga orientalis L. Growing in Turkey - Zehra Küçükbay , F.; Kuyumcu, Ebru; Yildiz, Bayram (Asian Journal of Chemistry, 2013)
The essential oil obtained from the aerial parts of Ajuga orientalis L. (Lamiaceae) was analyzed by using GC and GC-MS. Thirty compounds representing 95.4 % of the oil were identified. The main compounds were phytol (36.7 %), n-hexadecanoic acid (14.2 %) and dodecanoic acid (12.2 %).